Long-Term Health Effects of Artificially Colored Foods in Adults and Children: A Review of Scientific Literature on Attention Deficits, Carcinogenicity, and Allergy Risks - Ambroziewicz, Zuzanna Martyna; Siemiątkowski, Robert; Łata, Michał; Dowgiert, Szymon; Sikorska, Małgorzata; Kamiński, Jakub; Więcław, Katarzyna; Grabowska, Hanna; Chruściel, Joanna; Mąsior, Gabriela (Journal of Education, Health and Sport, 2024)
The widespread use of artificial food colorants in processed foods has raised concerns regarding their long-term health effects, particularly in sensitive populations like children. This review evaluates current scientific literature on the potential health risks associated with synthetic food colorants, including attention deficits, carcinogenicity, and allergenic responses. Synthetic dyes, such as tartrazine (E102) and Brilliant Blue FCF (E133), are highly valued for their stability and vibrancy but have been linked to neurobehavioral and allergenic effects. Evidence suggests that azo dyes may induce hyperactivity, learning impairments, and allergic reactions, particularly in children and those with a genetic predisposition to sensitivities. In contrast, natural pigments like curcumin (E100), chlorophyllin (E140), and anthocyanins (E163) exhibit anti-inflammatory and antioxidant properties, supporting cardiovascular, cognitive, and cancer-preventive health benefits, though their stability in food applications presents a challenge. The review also highlights regulatory responses, such as the European Union’s mandatory labeling requirements, which aim to reduce synthetic dye exposure in high-risk groups. Given the adverse effects associated with synthetic colorants, there is an increasing shift toward natural alternatives. However, enhancing the bioavailability and stability of these natural compounds is essential for their broader adoption. This comprehensive analysis underscores the need for balanced, evidence-based regulation and consumer education to promote safer food colorant choices and supports ongoing research into functional food colorants that offer both aesthetic appeal and health benefits.